How Price, Promotion, and Financial Risk Shape Purchase Intention: Evidence from the Construction Industry in Magelang - Kartika, Kristi; Aprianingsih, Atik (Airlangga Journal of Innovation Management, 2025)
Price and promotion are important factors that determine purchase intention, but their relationship with perceived risk has not been widely explored, especially in the context of the construction industry. This study aims to find the impact of price and promotion on the purchase intention in construction services, with the perceived financial risk as the mediation variable. A quantitative approach was used in this study, where the data were collected through a constructed questionnaire. The questionnaire was designed to simultaneously filter respondents, leaving only 144 responses selected for further analysis, namely from those who were planning to renovate their homes, were interested in using construction services, and lived in the Magelang area and its surroundings. The analysis utilized SmartPLS4 for Partial Least Squares Structural Equation Modeling (PLS-SEM). The analysis showed that the price and promotion influence the purchase intention, as well as the promotion affecting the perceived financial risk. The mediation results show that perceived financial risk does not have a significant influence on purchase intention as a mediating variable between price and purchase intention, as well as between promotion and purchase intention. These findings provide insight into how price and promotions shape purchase intentions without considering potential financial losses. This research contributes to construction businesses' efforts to improve purchase intentions, which can aid in new project acquisitions.